1989
DOI: 10.1007/bf01540265
|View full text |Cite
|
Sign up to set email alerts
|

Lactitol in prevention of recurrent episodes of hepatic encephalopathy in cirrhotic patients with portal-systemic shunt

Abstract: Recurrent episodes of hepatic encephalopathy (HE) frequently occur in surgically shunted cirrhotic patients. The prevention of these episodes is based mainly on the long-term use of lactulose. Recently, lactitol, a nonabsorbable disaccharide similar to lactulose, has been proposed as an alternative in the management of HE. It has the advantage of being better tolerated and producing a more predictable catharsis. The effects of the two agents were compared in a controlled randomized study lasting six months inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…The frequency of infection as precipitating factor appears to be declining and gastrointestinal bleeding appears to be increasing [14] . Lactulose is effective in the management of hepatic encephalopathy [15] and in the prevention of secondary episodes of encephalopathy [16] . Gut irrigation with paromomycine plus lactulose had been found to be effective in the prevention of encephalopathy devolvement after upper GIT bleed in previous trials [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of infection as precipitating factor appears to be declining and gastrointestinal bleeding appears to be increasing [14] . Lactulose is effective in the management of hepatic encephalopathy [15] and in the prevention of secondary episodes of encephalopathy [16] . Gut irrigation with paromomycine plus lactulose had been found to be effective in the prevention of encephalopathy devolvement after upper GIT bleed in previous trials [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The median duration of treatment was 15 days (range 5-360 days). Lactitol has also been used in treatment of HE and meta-analysis showed no statistical differences in percentage of improved patients after lactitol or lactulose while slightly higher frequency of flatulence in patients treated with lactulose compared with lactitol [15][16][17][18][19] (Table 1).…”
Section: Clinical Efficacy Of Non-absorbable Disaccharidesmentioning
confidence: 99%
“…It is available in a highly soluble crystalline powder form and is reported to be less sweet in taste than lactulose. Clinical trials have reported lactitol dosages of 10-12 g every 6 hours, titrated to two bowel movements daily to be effective in treatment of HE (31,33). Disaccharides (both lactulose and lactitol) remain undigested until they reach the colon, where they get metabolized by the bacteria in the colon to acetic and lactic acid.…”
Section: Non-absorbable Disaccharides and Mechanism Of Actionmentioning
confidence: 99%
“…Lactulose and lactitol both have been used for the treatment of HE and lactulose has been compared with lactitol in various studies (32,33,(50)(51)(52)(53)(54)(55)(56)(57) (Table-2). Morgan et al(32) enrolled twenty-five cirrhotic patients experiencing 28 episodes of acute hepatic encephalopathy which were randomized blindly to treatment with either lactitol (n = 15) or lactulose (n = 13).…”
Section: Lactulose Versus Lactitol For the Treatment Of Hepatic Encepmentioning
confidence: 99%
See 1 more Smart Citation